FUNGSI MADRARAH DALAM PENGEMBANGAN ILMU PENGETAHUAN ISLAM - Ansaria, Naila; Siregar, Ummu Habibah (Proceeding International Seminar of Islamic Studies, 2024)
This research is entitled about the function of madrasas in the development of Islamic science. This title was taken in order to find out how big the function and influence of madrasas are in the development of Islamic science. Madrasas also use methods that play a very a very important role in transmitting religious knowledge. Like verbal transmission. This method is believed to be a powerful method, as the previous sheikhs taught their knowledge directly to their students. So, the result of this reseach are that madrasas are very influential in the development of Islamic education. Then these madrasas graduates brought their Islamic knowledge into their careers in various institutions and in social life so that islamic knowledge continues to develop to this day.